Bridging algebra and geometry: a statistical analysis of algebraic applications in geometrical concepts - Paul, Ranjit; Sahidullah, Md. (International Journal of Advanced Mathematical Sciences, 2025)
To this purpose, the current research studied spatial reasoning considering geometry with a special emphasis on how algebra may play into ‎impacting students' geometric comprehension. A mixed-methods strategy was adopted, including questionnaires and evaluations to obtain ‎data from students about both their algebraic abilities as well as spatial reasoning competence. The findings reveal a direct association be-‎tween algebraic equation performance and spatial thinking, with a r = 0.65 correlation in the Pearson coefficient. Moreover, the multiple ‎regression analysis suggests that algebraic ideas strongly predict problem-solving performance (R² = 0.78 (p≤.000). Overall, the findings ‎underline algebra as a doorway to geometric reason and so bolster a justification for integrating algebra with geometry in education. ‎Through interdisciplinary teaching approaches, educators may create a more integrated mathematical framework among pupils, consequently ‎increasing spatial thinking and overall results in mathematics. The implications for mathematics education are substantial, demonstrating that ‎a more thorough knowledge of algebra may enhance geometric problem-solving. but is not only a driver for improved educational results, ‎but will also mean our students are being appropriately equipped to take the advanced applications in sectors such as engineering and computer science, where both algebraic and geometric thinking matter immensely. The findings underscore the relevance of educational techniques that offer a clear, cohesive depiction of mathematics for supporting student learning gains‎.